SURVEI DAN PEMETAAN TOPOGRAFI LAHAN DAN GEDUNG PONDOK PESANTREN AL-IHSAN BENTOK DESA BENTOK KAMPUNG - Shodiq, Adib Muhammad; Sobatnu, Ferry; Inayah, Nurul; Batara, Yastin David (Politeknik Negeri Banjarmasin, 2020)
Pondok Pesantren Al-Ihsan Bentok is located in Bentok Kampung village, Bati-Bati sub-district, Tanah Laut District. It is the sixth branch of Pondok Pesantren Al-Ihsan Tahfizh located in Banjarmasin city. As the new branch, they are facing some problems. The high demand from parents about making their son and daughter tahfizh and tahfizhah, causes the new branch's lack of infrastructure. Because of that problem, the management of Pondok Pesantren Al-Ihsan Bentok decides to build some new infrastructure. In order to build new infrastructure, they need Detailed Engineering Design (DED). One of the components of the DED document is Pondok Pesantren Al-Ihsan Bentok topographic map. Through D-III Teknik Geodesi community service team, Pondok Pesantren Al-Ihsan Bentok topographic map will available. It helps the management of Pondok Pesantren Al-Ihsan Bentok to complete the DED document. The implementation of the topographic survey used the terrestrial survey method. The survey used instruments like Total Station and GPS receiver Handheld type. The topographic survey started by build a mapping network, survey all of the details in Pondok Pesantren Al-Ihsan Bentok and draw the map digitally. All the details include existing buildings, roads, Pondok Pesantren Al-Ihsan boundary, sewer, river, and contour. The result is a Pondok Pesantren Al-Ihsan topographic map with a scale of 1:3.500. Based on the topographic map, the Pondok Pesantren Al-Ihsan surface area is 113266.751 square meters or 11.33 hectares. The male dormitory area is 500 m2 and the female dormitory area is 650 m2.